ANALYSIS OF FANO RESONANCE IN SPHERICAL TRIMER STRUCTURE USING T-MATRIX DECOMPOSITION - Natanael, Misael
Much attention from researchers have been focused on nanophotonics phenomena especially Fano resonances due to their asymmetrical spectral features in optical spectra. The emergence of Fano resonance in a structure can be explained in terms of coupling between non-orthogonal modes supported by the structure. Identification of these modes can be done using T-Matrix formulation. In scatterer which consists of many particles, T-Matrix can be formulated in local coordinate of each particle and global coordinate which represent the whole system. Using the eigenvalue decomposition (EVD) on global T-Matrix, the generated eigenmodes of the system can be found. Using computational program based on the T-Matrix formulation, we conduct an analysis of Fano resonance in spherical trimer structure which consists of dimer structure and single nanosphere with different materials (gold and silicon in this case). In this research, two types of structure are considered which are gold dimer – silicon nanosphere and silicon dimer – gold nanosphere. These two structures exhibit Fano profile in the cross section spectra. The observed Fano profiles correspond to the interference terms resulting from coupling between non-orthogonal eigenmodes in the system.